The quick-reference guide to biblical counseling : personal and emotional issues - Clinton, Timothy E., 1960-; Hawkins, Ronald E. (Grand Rapids, Mich. : Baker Books, 2009)
Hurting people need help. But sometimes those who are faced with helping the hurting could use a little more information about the problems that needy people bring to them. The Quick-Reference Guide to Biblical Counseling provides the answers. It is an A-Z guide for assisting people-helpers-pastors, professional counselors, youth workers, and everyday believers-to easily access a full array of information to aid them in (formal and informal) counseling situations. Issues addressed include addictions, forgiveness, sexual abuse, worry, and many more. Each of the 40 topics covered follows a helpful eight-part outline and identifies: 1) typical symptoms and patterns, 2) definitions and key thoughts, 3) questions to ask, 4) directions for the conversation, 5) action steps, 6) biblical insights, 7) prayer starters, and 8) recommended resources.
Abortion -- Addictions -- Adultery -- Aging -- Anger -- Bitterness -- Burnout -- Death -- Decision making and the will of God -- Depression -- Discouragement -- Divorce - Domestic violence -- Eating disorders -- Envy and jealousy -- Fear and anxiety -- Forgiveness -- Grief and loss -- Guilt -- Homosexuality -- Loneliness -- Love and belonging -- Mental disorder -- Money crisis -- Pain and chronic pain -- Parenting -- Perfectionism -- Pornography -- Prejudice -- Premarital sex -- Self-esteem -- Sexual abuse in childhood -- Singleness -- Spiritual warfare -- Stress -- Suffering -- Suicide -- Trauma -- Workaholism -- Worry.
Includes bibliographical references (p. 281-283).
Keywords: Counseling -- Religious aspects -- Christianity -- Handbooks, manuals, etc; Bible -- Psychology -- Handbooks, manuals, etc; Pastoral counseling -- Handbooks, manuals, etc; Bible -- Use -- Handbooks, manuals, etc